A new species of Losdolobus Platnick & Brescovit 1994 (Araneae: Orsolobidae) from Argentina with notes on its ecology and distribution - Pompozzi, Gabriel (Zootaxa, 2015)
A new species of Losdolobus, L. nelsoni sp. nov., is described based on females and males collected from grasslands in the mountains of southern Buenos Aires province, Argentina. Additionally, the phenology of this new species is presented and some aspects of the biogeography and distribution of the genus are discussed.